Rekonstruksi Filsafat Pendidikan Anak Perspektif Al-Ghazali Berbasis Fitrah dalam Penguatan Karakter Religius Anak Usia Dini di Era Digital - Ulya Ainur Rofi’ah; Jauharotina Alfadhilah (Alzam: Journal of Islamic Early Childhood Education, 2026)
The development of the digital era has brought significant challenges to early childhood education, particularly in maintaining a balance between technological advancement and the strengthening of religious character. Uncontrolled exposure to digital technology may negatively affect children’s moral and spiritual development. Therefore, an educational approach that integrates Islamic values with contemporary demands is urgently needed. This study aims to reconstruct the philosophy of child education from the perspective of Al-Ghazali based on the concept of fitrah in strengthening the religious character of early childhood in the digital era. This research employs a qualitative approach using a library research method, drawing on the classical works of Al-Ghazali as well as relevant contemporary educational literature. Data were analyzed through descriptive-analytical techniques, including data reduction, interpretation, and conclusion drawing. The findings reveal that the concept of fitrah in Al-Ghazali’s perspective refers to the innate human potential inclined toward goodness, which must be nurtured through education oriented toward moral development and spiritual purification (tazkiyatun nafs). A fitrah-based learning model is capable of integrating cognitive, affective, and spiritual aspects through play-based activities, value habituation, and teacher exemplification. Furthermore, this concept aligns with modern educational approaches while offering a stronger emphasis on spiritual dimensions. In the digital era, this approach serves as a normative foundation for guiding the wise and meaningful use of technology. In conclusion, the reconstruction of child education philosophy from the perspective of Al-Ghazali based on fitrah provides a strategic solution for strengthening early childhood religious character in the digital era. This approach results in a holistic, adaptive, and character-oriented educational model